Structural Integrity Management For Fixed Offshore Platforms in Malaysia - Sambu Potty , Narayanan (2009)

(untitled)
Structural Integrity Management is important for the protection of offshore crew, environment, business assets and company and industry reputation. API RP 2A and ISO 19902 contained guidelines for assessment of existing platforms which do not specifically cater for Malaysia. There are about 90 platforms in Malaysia exceeding their design life. The Petronas Carigali Sdn Bhd uses the Asset Integrity Management System and the very subjective RBI Program and currently doesn’t have a standalone Technical Standard, which this study proposes. A case study on SMG-A platform in Sabah is also reported.